Does carbon labelling encourage the consumption of low‐emission meat products? Evidence from China - Yuan, Rao; Tang, Zhengmin (The Australian journal of agricultural and resource economics, 2025)
By combining a hypothetical labelled‐choice experiment and a between‐subject design experiment, this study explores the influence of carbon labels on low‐emission meat consumption. The results reveal that carbon labels are effective in encouraging consumers to choose low‐emission conventional meat products. However, carbon labels are ineffective in persuading consumers to choose novel meat alternatives. Additionally, the results suggest that the efficiency of carbon labels depends on their format. The traffic‐light carbon label was identified as the most effective, reducing carbon emissions from meat consumption by 21.55%, followed by the carbon‐reduction label at 18.07% and the carbon‐neutral label at 2.6%. The findings raise implications for policymakers in developing standards for carbon labels.